2003
DOI: 10.2741/1105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular physiology and sleep

Abstract: Sleep is a natural periodic suspension of consciousness during which processes of rest and restoration occur. The cognitive, reparative and regenerative accompaniments of sleep appear to be essential for maintenance of health and homeostasis. This brief overview will examine the cardiovascular responses to normal and disordered sleep, and their physiologic and pathologic implications. In the past, sleep was believed to be a passive state. The tableau of sleep as it unfolds is anything but a passive process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 124 publications
1
11
0
1
Order By: Relevance
“…Our finding that adrenergic C1 neurons are activated during REMS-like state provides a mechanistic explanation for the mean arterial blood pressure increases that occur during transitions from slow-wave sleep to REMS [113], [114], [115]. Indeed, the average blood pressure increases that we observed during REMS-like episodes were significant and of a similar magnitude as those observed on the average during REMS [113], [114], [115] (as discussed in the preceding section, the model that we used does not generate phasic events of REMS; accordingly, we cannot comment on blood pressure variability that is another characteristic feature of natural REMS but is absent from the carbachol models).…”
Section: Discussionmentioning
confidence: 72%
“…Our finding that adrenergic C1 neurons are activated during REMS-like state provides a mechanistic explanation for the mean arterial blood pressure increases that occur during transitions from slow-wave sleep to REMS [113], [114], [115]. Indeed, the average blood pressure increases that we observed during REMS-like episodes were significant and of a similar magnitude as those observed on the average during REMS [113], [114], [115] (as discussed in the preceding section, the model that we used does not generate phasic events of REMS; accordingly, we cannot comment on blood pressure variability that is another characteristic feature of natural REMS but is absent from the carbachol models).…”
Section: Discussionmentioning
confidence: 72%
“…This inflammation may induce a hypercoagulable state that could be directly involved in the pathogenesis of diseases such as coronary artery disease, although the exact mechanisms remain unknown. Many papers have linked poor sleep to increased risk of cardiovascular disease [10,25], and the role of systemic inflammation and hypercoagulable states resulting from disordered sleep or loss of sleep requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that sleep restriction with CM was associated with higher HR and lower HRV during non-REM stages (i.e., SWS and Stage II) as compared to sleep restriction with CA. Given the importance of SWS and non-REM sleep in cardiovascular restoration, 31 these findings suggest that recurrent or chronic circadian misalignment has adverse cardiovascular effects that are not readily corrected as soon as a normal daytime schedule is re-instated. The rate of recovery of nocturnal autonomous nervous system activity following abrupt shifts of the sleep-wake cycle needs further study to improve our understanding of the adverse cardiovascular consequences of shift work and design preventive strategies.…”
Section: Discussionmentioning
confidence: 99%